Transition from indirect to direct band gap in SiC monolayer by chemical functionalization: A first principles study. (January 2020) - Hoat, D.M.; Naseri, Mosayeb; Hieu, Nguyen N.; Ponce-Pérez, R.; Rivas-Silva, J.F.; Cocoletzi, Gregorio H.
Abstract: First-principles total energy calculations based on the pseudopotential plane-wave method, within the density functional theory, have been carried out to investigate the structural and electronic properties of the pristine and chemically functionalized SiC monolayer. Results show that the SiC monolayer has an indirect band gap, whose value calculated within the PBE and HSE06 theories is 2.492 and 3.264 eV, respectively. Structurally, the chemical functionalization with halogen atoms (F and Cl) generates a buckling in the SiC monolayer. Interestingly, the indirect-to-direct band gap transformation may be achieved by the chemical functionalization as all the fluorinated, chlorinated and Janus functionalized SiC monolayer are direct semiconductors. The electronic band gap of these chemically functionalized monolayers are in the range of [1.502 and 1.978 eV] and [2.508 and 2.998 eV] predicted by PBE and HSE06 functionals, respectively. Our work is expected to pave an effective way to tune the SiC monolayer electronic structure for practical applications. Highlights: Chemical functionalization effect on the structural and electronic properties of SiC monolayer is investigated using DFT calculations. SiC monolayer has a planar structure and a buckling emerges with the chemical functionalization. SiC monolayer is an indirect semiconductor with band gap value of 2.492(3.264) eV predicted by PBE(HSE06) theory. Chemical functionalization induces indirect-to-direct band gap transition and reduces the band gap value.